Ensuring patient safety by rational choice of color masterbatch for medical device applications—A case study investigating the properties of an ABS/SAN blend colored by different masterbatches based on styrenic polymers - Guenther, Bjoern; Kremser, Thomas; Susoff, Markus; Formanek, Petr; Fery, Andreas; Wiessner, Sven (Journal of Applied Polymer Science, 2022)
The coloration of plastics is an important quality feature of medical devices, and it is most frequently done by using masterbatches. This study investigates the influence of masterbatches with different carrier resins on the impact resistance and the morphology of an acrylonitrile-butadiene-styrene (ABS)/styrene-acrylonitrile (SAN) blend. The experimental results were compared with thermodynamical models based on Hansen and Flory–Huggins theory. The models, as well as notched impact testing, indicated strong immiscibility and incompatibility when using a masterbatch carrier based on polystyrene (PS). Immiscibility was confirmed by morphology studies that revealed the formation of PS-droplets with increasing masterbatch content. Masterbatches based on ABS and SAN showed no significant impact and theoretical calculations were in good accordance with mechanics and morphology. The proposed theoretical calculation of solubility between blend partners potentially allows a prediction for selecting a suitable masterbatch carrier.
CRIS-Team Scopus Importer:2022-04-14